Le Jeu de la Hache - Olivier Dupuis; Vincent Deluz (Acta Periodica Duellatorum, 2017)
Twenty-six years after the first edition and translation by Sydney Anglo in 1991 of the anonymous manuscript Le Jeu de la hache , many elements can still be significantly improved. This paper offers a completely new critical edition of the text, and a major revision of the translation. This article includes a detailed glossary as well as notes to discuss the many ambiguous passages in the original text. Finally, the studies of the language, the vocabulary, the dialect, the writing style and the physical document make it possible to refine the dating of the manuscript to the third quarter of the fifteenth century, between 1460 and 1485, and its origin, probably Flanders or Wallonia in the entourage of the dukes of Burgundy.